Secure architectural design of commercial buildings - Tuqa Mahmood Hameed; Abdullah Saadoon Salman Almaamouri (Iraqi Journal of Architecture and Planning, 2018)
The study deals with the concept of security as one of the concepts that affect the process of architectural design. Despite the development of architecture, one of its main objectives remains that the buildings are general and commercial, especially safe, regardless of the degree of urbanization or simplicity of thebuilding, especially in view of the increasing threat of terrorist and criminal threats, Especially when human threats are common and are practiced for various reasons in the 21st century. The research problem is thus (the emergence of the cognitive need to study the safe design of human threats to commercial shoppingcenters). The research aims to clarify the principles of architectural design safe from human threats, as well as to know the impact of urban and architectural characteristics on the level of security of shopping malls commercial fortified, and accordingly the research assumes that the dimensions of safe design has apositive impact in the sustainability of shopping malls. In order to address the research problem and achieve the objectives of the research and validation of the hypothesis was first built knowledge framework, and then a comprehensive theoretical framework for safe design in shopping centers extracted from the architectural proposals to reflect the final version in three main dimensions, namely: principles of safe design of the criminal act and mechanisms, and principles of safe design Of the terrorist act and its mechanisms, and the urban and architectural characteristics affecting security. The first is to control the security design process according to all of its indicators. The second is the difference in the design indicators according to the nature of the threat, but they are integrated together in order to achieve security for the shopping centers andthe safety of the pioneers .